Microstructural evolution and phase transformation in twinning-induced plasticity steel induced by high-pressure torsion. (1st May 2016) - An, X.H.; Lin, Q.Y.; Sha, G.; Huang, M.X.; Ringer, S.P.; Zhu, Y.T.; Liao, X.Z.
Abstract: The microstructural evolution of twinning-induced plasticity steel during high-pressure torsion (HPT) processing at 573 K was systematically evaluated. Due to the high processing temperature, the formation of a homogeneous nanostructure was primarily dominated by complicated dislocation and grain boundary activities in lieu of deformation twinning. Apart from the grain refinement process, phase transformation took place at late stages of deformation, resulting in the microstructural fingerprint of equaxied nanograins with multiple phases in the steel. On account of remarkable elemental redistribution, the diffusion-controlled nature of the transformation was convincingly identified. During the transformation, although the cementite also initially formed, austenite eventually decomposed into ferrite and Mn-riched M23 C6 carbide, implying that Mn is the pivotal alloying element for the transformation kinetics. Owing to the sluggish bulk diffusivity of Mn, it is proposed that a high density of defects, nanostructures and the HPT processing play a crucial role in promoting the elemental diffusion and segregation and in stimulating the phase transformation. Graphical abstract: